Review and synthesis of IFPRI’s PIM funded program of work on agricultural insurance, 2012-2020 - Hazell, Peter B. R.; Timu, Anne G. (International Food Policy Research Institute, 2021)
This paper reviews and synthesizes IFPRI’s research program on agricultural insurance since 2009, a period that encompasses all the activities for which financial support from PIM was obtained during 2012-2020. The paper reviews activities that were undertaken, synthesizes and evaluates the research outputs, and uses case studies to assess some of the program’s development outcomes. The study also identifies knowledge gaps and suggests priorities for future research for IFPRI and the OneCGIAR on risk management and agricultural insurance. The methods used in this study were: a desk review of project documents, research outputs, and metrics on the use and influence of research outputs; and remotely conducted interviews with some IFPRI and PIM staff and individuals in partner organizations for select case studies.